1978
DOI: 10.1007/bf01843999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of a new allele of the rabbit group b Ck allotypes

Abstract: An inherited variant (b4(v)) of the rabbit kappa-chain allotype b4 is characterized by the presence of serine in place of alanine at position 121 and leucine in place of glutamine at position 124. The variant was traced through eight generations of a pedigreed rabbit family. Genetic analysis of this trait demonstrated that it is an allele of the other group b allotypes, and recent breedings have produced rabbits homozygous for this light-chain type. Two findings, other than the amino acid sequence differences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Elution was obtained with a gradient 0% B to 60% B in 1 h. The flow rate is 1 mL/min. light chain, obtained after allotypic suppression of a b4/b5 rabbit (Chersi et al, 1980), suggests that variations may exist among the constant regions of b5 chains, as has been previously shown for b4 (Strosberg et al, 1974;Sogn & Kindt, 1978) and for b6 (Emorine et al, 1979). Among the six differences between the b5 constant region described by Chersi and that of light chain 2699, two (leucine for valine at position 195 and proline for alanine at position 196) could be technical, since they were deduced from amino acid compositions in Chersi et al report.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Elution was obtained with a gradient 0% B to 60% B in 1 h. The flow rate is 1 mL/min. light chain, obtained after allotypic suppression of a b4/b5 rabbit (Chersi et al, 1980), suggests that variations may exist among the constant regions of b5 chains, as has been previously shown for b4 (Strosberg et al, 1974;Sogn & Kindt, 1978) and for b6 (Emorine et al, 1979). Among the six differences between the b5 constant region described by Chersi and that of light chain 2699, two (leucine for valine at position 195 and proline for alanine at position 196) could be technical, since they were deduced from amino acid compositions in Chersi et al report.…”
Section: Discussionmentioning
confidence: 67%
“…The b4 Var differs from b4 by two residues (serine for alanine at position 121 and leucine for glutamine at position 124). Genetic data show that b4 is an allele of b4 Var (Sogn & Kindt, 1978). Several different residues have also been observed in the b4 light chain sequence at position 172 (Am, Leu, and Val) (Appella et al, 1973;Chen et al, 1975;Van Hoegaerden & Strosberg, 1978).…”
Section: T-smentioning
confidence: 99%
See 1 more Smart Citation
“…Serological and chemical studies have demonstrated to date the existence of five polymorphic forms of the domestic rabbit K light (L) chain allotypes designated b4, b5, b6, b9, and b4var (1)(2)(3)(4)(5)(6). Extensive chemical differences in the constant (C) regions of b4, b5, b6, and b9 molecules have been reported (7)(8)(9) and are thought to reflect the expression of the antigenic determinants of the b allotypes (10).…”
mentioning
confidence: 99%
“…This led us to the view that the structural genes of the light chain might determine the probability of effective contact between Ig receptor and antigen (Szymanska et al, 1981) In rabbits heterozygous at the kappa light chain allotypic locus (Ab) the two allelic genes are not equally expressed. A preponderance of Ab4 over all other Ab alleles has been documented and is known as the 'pecking order' (Chou et al, 1967(Chou et al, , 1972(Chou et al, , 1974Sogn & Kindt, 1978). It is likely that this pecking order results from different probabilities of antigen capture by different allotypically marked receptors.…”
mentioning
confidence: 99%